Pengaruh Pemberian Limbah Tepung Roti Afkir Dalam Ransum Terhadap Recahan Karkas Ayam Kampung - I Gusti Agung Putra Narayana I gusti agung putra narayana; Ni Ketut Sri Rukmini; Ni Ketut Etty Suwitari (GEMA AGRO, 2022)
The purpose of this study was to determine the effect of replacing corn with discarded bread flour on carcass crumbs of super free-range chicken during a 10-week rearing period and the level of use of rejected bread flour in what percentage will have an effect on carcass crumbs of super free-range chicken aged 10 weeks. The design used was a completely randomized design (CRD) with 5 (five) treatments and 3 (three) replications so that there were 15 cage units and each unit consisted of 5 free-range chickens and 75 free-range chickens were used. The treatments were as follows: rations without Bread Flour (TRA) (P0), rations containing 10% TRA (P1), rations containing 20% ​​TRA (P2), rations containing 30% TRA (P3) and rations containing 40% TRA (P4 ). The results showed that the replacement of corn with rejected bread flour had a significant (P<0.05) to very significant (P<0.01) effect on breast weight, wing weight, thigh weight, and back weight of super free-range chickens during the 10-month rearing period. week. The level of use of the best rejected bread flour is 20% with the weight of the chest, thighs, wings and back of 113.70 g/head, 154.30 g/head, 63.43 g/head and 101.13 g/head, respectively